Freedom of Religion in the 1945 Constitution and the Medina Charter: A Comparative Analysis in the Perspective of Siyasah Dusturiyah - Fadhlurrahman, Fauzan; Saebani, Beni Ahmad; Sutiana, Yana (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the concept of religious freedom in the 1945 Constitution of Indonesia and the Medina Charter from the perspective of Siyasah Dusturiyah (Islamic Constitutional Law). Using a comparative, normative, and juridical approach, this research examines the similarities and differences in the principles of religious freedom between these two constitutional documents. The findings reveal that both the Medina Charter and the 1945 Constitution guarantee religious freedom within the framework of national unity and integrity. The Medina Charter, as the first written political document in Islamic history, recognizes non-Muslims as part of the ummah (nation) and guarantees their right to practice their religion freely, as stated in Articles 1 and 25. Similarly, the 1945 Constitution affirms religious freedom in Article 29 paragraph (2) and Chapter XA Article 28E paragraph (1). From the perspective of Siyasah Dusturiyah, both documents reflect the principles of shura (consultation), justice ('adl), and maslahah (public interest) in regulating religious freedom. The study concludes that the principles of religious freedom in Islam, as manifested in the Medina Charter, are highly relevant to and compatible with the constitutional framework of modern Indonesia. This research contributes to the theoretical development of Islamic constitutional law and provides practical insights for strengthening religious freedom policies in Indonesia.